Fernando Hidalgo Nistri. La República del Sagrado Corazón. Quito: Universidad Andina Simón Bolívar, Sede Ecuador / Corporación Editora Nacional, 2013, 311 pp. - Fernández de Córdova, Carlos Espinosa (Procesos. Revista Ecuatoriana de Historia, 2014)
S.R